Pelatihan untuk masyarakat Indonesia di Jerman “women leadership” - Wazni Azwar (Unri Conference Series: Community Engagement, 2020)
Community service as one of the tasks in the Tri Dharma of Indonesian Higher Education has tried to help the Indonesian people in Frankfurt Germany to facilitate community empowerment efforts, especially women with the theme "Women Leadership". In Government Studies, it is known that the core of Government Studies is leadership, and the core of leadership is decision making. In Islamic values, ​​it is also known that everyone is a leader. Thus, women and leadership are two related words. The question is, how is the relationship? How is this relationship implemented in the Frankfurt Indonesian Muslim Community and in everyday life? It can be said that the active role of women in the Frankfurt Indonesian Mosque can be seen in real terms. Both men and women have learned Islam and applied Islamic values ​​together. This community service was divided into three stages. First, registration by email. Second, filling out the questionnaire and sending it via email. Third, a general lecture session on women leadership using the Indonesian language and continued with a question and answer session at the Frankfurt Indonesian Mosque. The implementation of the service has gone smoothly and was attractive to the participants. This can be seen from the third stage which was originally scheduled for about two hours to four hours. The participant's response was positive with intense interactive dialogue during the presentation of the material. This activities results pattern of leader personal characteristic from members. Hopefully, this is becoming a great capital to born a great women leader in the future